ESG, Firm Value, and Life Cycle: Evidences from South East Asia - Xaviera, Areta; Febrianto, Rahmat; Widiastuty, Erna; Iswardi, Iswardi (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2024)
This study investigates the impact of ESG performance on future firm value, considering the company's phase in the life cycle. The sample consists of non-financial companies listed in five Southeast Asian (SEA) countries. Data were collected from the Refinitiv Eikon Database, with samples determined using a purposive sampling technique. The study covers the period from 2013 to 2022, resulting in 1,080 firm-year observations. Using multiple regression analysis, the study finds that ESG performance is related to the next year's firm value in SEA companies. ESG performance impacts firm value only when the company is in the mature stage, while mixed relationships were observed when individual ESG dimensions were tested. These findings support the notion that the effects of ESG-related performance may not be immediately reflected in the current years firm value but rather in the future.